A Student's Guide to the History and Philosophy of Yoga - Connolly, Peter (London : Equinox Pub., 2007)
The book is aimed at both university students taking courses in Comparative Religion and Philosophy and practitioners of yoga who seek to go beyond the activity and explore its spiritual dimensions. Hence, it presents yoga in the context of its historical evolution in India and seeks to explain the nature of its associations with various metaphysical doctrines.
Cover; Contents; Abbreviations; Sanskrit Letters and their Pronunciation; Introduction; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chapter 6; Chapter 7; Chapter 8; Notes; Introduction; Chapter 1; Chapter 2; Chapter 3; Chapter 4; Chapter 5; Chapter 6; Chapter 7; Chapter 8; Bibliography; Index.
Description based on print version record.
Keywords: Yoga -- History; Yoga; Yoga -- History; PHILOSOPHY / Hindu; Electronic books